Executive Function and Behavioral Problems in Students with Visual Impairments at Mainstream and Special Schools. (July 2015) - Heyl, Vera; Hintermair, Manfred
Introduction: In this study, executive function of school-aged children with visual impairments (that is, those who are blind or have low vision) is examined in the context of behavioral problems and communicative competence. Methods: Teachers assessed the executive function of a sample of 226 visually impaired students from mainstream schools and schools for students who are visually impaired, using a German version of the Behavior Rating Inventory of Executive Function (BRIEF-D) and a questionnaire measuring communicative competence and behavioral problems (German version of the Strengths and Difficulties Questionnaire; SDQ-D). Results: The results showed highly significant differences in all domains of executive function: the visually impaired students consistently scored more poorly compared to a normative sample of sighted children, even when visually impaired students with additional disabilities were not taken into account. A regression analysis revealed the significance of executive function for behavioral problems among students with visual impairments. Discussion: The findings demonstrate that a wide range of executive function domains that are significant for socioemotional development are not sufficiently developed in many visually impaired students. This lack of development seems to be particularly true for students who attend special schools. Implications for practitioners: In educational concepts for visually impaired students, a specific and early focus on competencies such as attention shifting and emotional understanding seems to be necessary, especially in the context of inclusion. Moreover, reinforcing communicative competence might also enhance the development of executive function and help to reduce behavioral problems.